Comparison of flexible ureteroscopy in the treatment of 1–2 cm single nephrolithiasis and multiple nephrolithiasis - Lv, Guangda; Zhou, Yongheng; Qi, Wenqiang; Zhong, Minglei; Li, Rongyang; Zhu, Yaofeng (Frontiers in Surgery, 2023)
Abstract Objective To compare the efficacy of flexible ureteroscopy for single urinary stones with that of multiple urinary stones. Methods A retrospective study was conducted on patients who underwent flexible ureteroscopy in Qilu Hospital of Shandong University from January 2016 to March 2021. Propensity score matching was used to match patients with no statistical difference in preoperative clinical data, and they were divided into solitary calculi and multiple calculi two groups. The postoperative hospital days, operation time, complications and stone free rate were compared between the two groups. And multiple stones were divided into high group (S-ReSc >4) and non-high group (S-ReSc ≤4) for analysis. Results 313 patients were counted. After propensity score matching, 198 patients were finally included in the study. There were 99 cases in the solitary stone group and the multiple stone group. There were no significant differences in postoperative hospital days, complications and stone free rate between the two groups. The operation time of patients with solitary stone group was significantly shorter than that of patients with multiple stones (65.00min, 45.00min VS 90.00min, 50.00min, P<0.001). The SFR of high group in the multiple stones group was significantly lower than that in the non-high group (7, 58.3% VS 78, 89.7%, P=0.013). Conclusion Despite the longer operation time, flexible ureteroscopy has similar outcomes in the treatment of multiple (S-Rec≤4) compared to solitary calculi. Although, this doesn’t apply when S-ReSc >4.